Ring Finger Protein 11 acts on ligand‐activated EGFR via the direct interaction with the UIM region of ANKRD13 protein family. (11th February 2020) - Mattioni, Anna; Boldt, Karsten; Auciello, Giulio; Komada, Masayuki; Rappoport, Joshua Z.; Ueffing, Marius; Castagnoli, Luisa; Cesareni, Gianni; Santonico, Elena
Abstract : RING finger protein 11 (RNF11) is an evolutionary conserved Really Interesting New Gene E3 ligase that is overexpressed in several human tumours. Although several reports have highlighted its involvement in crucial cellular processes, the mechanistic details underlying its function are still poorly understood. Utilizing stable isotope labelling by amino acids in culture (SILAC)‐based proteomics analysis, we identified 51 proteins that co‐immunoprecipitate with wild‐type RNF11 and/or with its catalytically inactive mutant. We focused our attention on the interaction of RNF11 with Ankyrin repeat domain‐containing protein 13 (ANKRD13)s family. Members of the ANKRD13 family contain ubiquitin‐interacting motifs (UIM) that recognize the Lys‐63‐linked ubiquitin (Ub) chains appended to Epidermal growth factor receptor (EGFR) soon after ligand binding. We show that ANKRD13A, ANKRD13B and ANKRD13D form a complex with RNF11 in vivo and that the UIMs are required for complex formation. However, at odds with the conventional UIM binding mode, Ub modification of RNF11 is not required for the interaction with ANKRD13 proteins. We also show that the interaction between ANKRD13A and RNF11 is modulated by the EGF stimulus and that a complex formed by ANKRD13A, RNF11 and activated EGFR is transiently assembled in the early phases of receptor endocytosis. Moreover, loss of function of the E3 ligases Itchy E3 ubiquitin‐protein ligase (ITCH) or RNF11, respectively, abrogates or increases the ubiquitination of endogenous ANKRD13A, affecting its ability to bind activated EGFR. We propose a model whereby the ANKRD13 proteins act as molecular scaffolds that promote the transient formation of a complex between the activated EGFR and the E3 ligases ITCH and RNF11. By regulating the ubiquitination status of ANKRD13A and consequently its endocytic adaptor function, RNF11 promotes sorting of the activated EGFR for lysosomal degradation. Abstract : We used a stable isotope labelling by amino acids in culture‐based proteomics approach to identify 51 proteins interacting with RING finger protein 11 (RNF11). We focused on Ankyrin repeat domain‐containing protein 13A (ANKRD13A) that promotes the rapid internalization of activated Epidermal growth factor receptor (EGFR). This process depends on the level of ANKRD13A ubiquitination. RNF11, in combination with Itchy E3 ubiquitin‐protein ligase (ITCH), modulates ANKRD13A mono‐ubiquitination and thus promotes sorting of activated EGFR to lysosome for degradation. Lastly, RNF11 is the first protein, identified so far, that directly binds the UIM motifs of ANKRD13A.